Social Navigation for Semantic Web Applications Using Space Maps - Matušíková, Katarína; Bieliková, Mária (Computing and Informatics, 2012)
In this paper we deal with personalized navigation in an open information space. Our aim is to support effective orientation in increasing amount of information accessible through the Web. We present a method for personalized navigation based on social navigation where the information space is represented by an ontology. Navigational information is obtained by following user footsteps. It is attached to information fragment mapped to the user goal and to description of this goal using an ontology. This information is used later to show the way to similar goals. We use ontology representation of the information space that supports the effective navigation and the navigational ability to deal with frequent changes of information content in open environments. We demonstrate the proposed method in the context of developed software tool PENA for personalized navigation support in labor supply domain.